Neonatal Mortality and Associated Factors in the Neonatal Intensive Care Unit of Gadarif Hospital, Eastern Sudan - Mohammed Ahmed A. Ahmed; Hyder M. Mahgoub; Abdullah Al-Nafeesah; Osama Al-Wutayd; Ishag Adam (MDPI AG, 2022)
Background: Neonatal mortality is a serious public-health issue, especially in Sub-Saharan African countries. There are limited studies on neonatal mortality in Sudan; particularly, there are none on eastern Sudan. Therefore, this study aimed to determine the incidence, causes and associated factors for mortality among neonates admitted to the neonatal intensive care unit (NICU) of Gadarif Hospital, eastern Sudan. Methods: This retrospective study included 543 neonates admitted to the NICU of Gadarif Hospital, eastern Sudan, between January and August 2019. Data were obtained from the hospital record using a questionnaire composed of sociodemographic data, neonatal and maternal information and neonatal outcomes. Logistic regression analyses were performed and the adjusted odds ratio (AOR) and 95% confidence interval (CI) were calculated. Results: Of the 543 neonates, 50.8% were female, 46.4% were low birth weight (LBW), 43.5% were preterm babies and 27% were newborns admitted after caesarean delivery. The neonatal mortality before discharge was 21.9% (119/543) of live-born babies at the hospital. Preterm birth and its complications (48.7%), respiratory distress syndrome (33.6%), birth asphyxia (21.0%) and infection (9.0%) were the most common causes of neonatal mortality. In multivariable logistic regression analysis, preterm birth (AOR 2.10, 95% CI 1.17-3.74), LBW (AOR 2.47, 95% CI 1.38-4.41), low 5 min APGAR score (AOR 2.59, 95% CI 1.35-4.99) and length of hospital stay <3 days (AOR 5.49, 95% CI 3.44-8.77) were associated with neonatal mortality. Conclusion: There is an increased burden of neonatal mortality in the NICU of Gadarif Hospital, eastern Sudan, predominantly among preterm and LBW babies.